Impact of Project Complexity and Environmental Factors on Project Success: A Case of Oil and Gas Sector of Pakistan - Farhaj Ishtiaq; Mirza Jahanzaib (Journal of Basic & Applied Sciences, 2017)
Oil and gas industry significantly contribute for economic development of countries enriched with petroleum resources. Mega projects of oil and gas sector usually face many challenges due to environmental issues, high level of risks, huge investments, tight schedules and interdependencies between project activities. Therefore keeping in view, the issues faced by oil and gas sector this study was made to analyze the impact of project complexity and environmental factors on success of oil and gas projects of Pakistan. Based upon hypothetical framework developed for this study, data collection was made from an oil and gas company of Pakistan. After which, data analysis was carried out by using a statistical technique known as structural equation modeling. Project complexity, environmental factors and project success were taken as constructs for model evaluation on AMOS. Analysis of data has concluded that project complexity has negative impact on project success whereas better control over environmental factors enhance the project success rate.